Inclusion of abandoned rhubarb stalk enhanced anaerobic fermentation of alfalfa on the Qinghai Tibetan Plateau. (March 2022) - Li, Ping; Zhao, Wenji; Yan, Lijun; Chen, Liangyin; Chen, Yulian; Gou, Wenlong; You, Minghong; Cheng, Qiming; Chen, Chao
Graphical abstract: Highlights: Alfalfa silage was prepared with abandoned rhubarb stalk (RS). High crude protein level was observed in RS-treated silage. Addition of RS promoted lactic acid production. Addition of RS restricted the growth of yeasts in silage. Addition of RS changed the bacterial community composition of silage. Abstract: To investigate the effects of lactic acid bacteria inoculant (LI) and abandoned rhubarb stalk (RS) on the anaerobic fermentation and bacterial community of alfalfa on the Qinghai Tibetan Plateau, the alfalfa was harvested and ensiled without (control) or with LI and RS at ambient temperature (5 ∼ 15℃) for 90 days. Addition of RS at ensiling increased ( P < 0.05) lactate, acetate and propionate contents, and decreased ( P < 0.05) the final pH value as compared with control. Addition of RS increased ( P < 0.05) the bacterial alpha diversity indices, while inherent Lactococcus lactis and/or Lactobacillus sakei dominated the anaerobic fermentation. In particular, addition of RS restricted the growth of yeasts and Lactobacillales at the early stage of ensiling, but continuously stimulated anaerobic fermentation. These indicates that RS could be used as additive to facilitate anaerobic fermentation of alfalfa.